Stewarding and power in networked learning - Whitworth, Andrew; Webster, Lee (Proceedings of the International Conference on Networked Learning, 2018)
A study is conducted of twenty groups, of 5-7 learners each, who are studying on a postgraduate course unit oriented toward development of professional practice in the field of educational technology. On the unit, students are assessed through their contributions to online discussion boards in which their groups are engaged in learning tasks that increase in complexity over the course and require them to make critical judgments about a range of informational and technological resources that can help the group meet its shared learning needs. Through the accumulation of these judgments, the group stewards its own digital habitat (Wenger et al 2009), modifying and enhancing the set of resources that the tutor provides to each group at the start of the course unit. The study investigates how this process draws on the power that flows in different ways through the course environment. Students discipline themselves and each other to conform to practices that they perceive as being those rewarded by the tutor, but they also resist this institutional power and authority when they introduce new resources and practices. The study shows how practices form at the very earliest stages of the formation of a community of practce, and bring with them a proto-hierarchy that supports the more complex information tasks but also introduces differentiation into the community. Visibility and scrutiny of the emerging practices and proto-hierarchy are what help the environment meet its learning needs and give students an experience of variation in power and authority that helps them develop informational practices in ways that are relevant to later work in professional settings.